Usos amorosos e identitarios de Esther Tusquets: ¿Hacia una transición inconclusa? - Katarzyna, Moszczyńska-Dürst (Wydawnictwo Naukowe UAM, 2013)
The aim of this study is to investigate the types of discourse, ideologies, values and models codified in Tusquet’s novels with respect to love and identity related narratives. In order to achieve our goal, we will apply the sociocritical theory regarding transition as well as love related theoretical patterns coined in sociology and psychology. The following questions shall be taken into consideration: which love and identity concepts are being depicted in the novels?, how do the love and identity discourses interact among themselves? Which types of discourse and which cultural models seem to be dominant in Tusquets’ narrative? and to what extent could the analyzed texts be seen as the inscription of an unaccomplished transition?
The Discursive Practice of Love and Identity in Esther Tusquet’s Novels: an unaccomplished transition?
Keywords: Tusquets; novel; Spanish transition; gender; ideology; sociocriticism